Long-term outcomes of acute treatment with cognitive therapy v. interpersonal psychotherapy for adult depression: follow-up of a randomized controlled trial. Issue 3 (24th May 2018) - Lemmens, Lotte H.J.M.; van Bronswijk, Suzanne C.; Peeters, Frenk; Arntz, Arnoud; Hollon, Steven D.; Huibers, Marcus J.H.
Abstract: Background: Although equally efficacious in the acute phase, it is not known how cognitive therapy (CT) and interpersonal psychotherapy (IPT) for major depressive disorder (MDD) compare in the long run. This study examined the long-term outcomes of CT v. IPT for MDD. Methods: One hundred thirty-four adult (18–65) depressed outpatients who were treated with CT ( n = 69) or IPT ( n = 65) in a large open-label randomized controlled trial (parallel group design; computer-generated block randomization) were monitored across a 17-month follow-up phase. Mixed regression was used to determine the course of self-reported depressive symptom severity (Beck Depression Inventory II; BDI-II) after treatment termination, and to test whether CT and IPT differed throughout the follow-up phase. Analyses were conducted for the total sample ( n = 134) and for the subsample of treatment responders ( n = 85). Furthermore, for treatment responders, rates of relapse and sustained response were examined for self-reported (BDI-II) and clinician-rated (Longitudinal Interval Follow-up Evaluation; LIFE) depression using Cox regression. Results: On average, the symptom reduction achieved during the 7-month treatment phase was maintained across follow-up (7–24 months) for CT and IPT, both in the total sample and in the responder sample. Two-thirds (67%) of the treatment responders did not relapse across the follow-up period on the BDI-II. Relapse rates assessed with the LIFE were somewhat lower. No differential effects between conditions were found. Conclusions: Patients who responded to IPT were no more likely to relapse following treatment termination than patients who responded to CT. Given that CT appears to have a prophylactic effect following successful treatment, our findings suggest that IPT might have a prophylactic effect as well.